اتجاهات طلبة كلية التمريض في جامعة تشرين نحو مهنة التمريض - بدور, هيام (Latakia University Journal -Medical Sciences Series, 2018)
Choosing to study nursing is affected by attitudes that carried by members of society toward it. The attitudes is a general, acquired, relative and emotional tendency that affects the specific motivations of the human being and plays a key role in guiding behavior towards achieving the goals and awareness of its results. This descriptive study aimed to identify the attitudes of 200 students from the Faculty of Nursing at Tishreen University towards the nursing profession and the difference, if any, in these attitudes according to the personal variables, students were selected with a stratified random sample manner during the period from 12/10/2016 until 22/11/2016, data were gathered with a predefined questionnaire for this purpose. the study found that the overall attitudes of the students towards the nursing profession was moderately positive, while it was highly positive in terms of ​​personal perception about the profession, and a positive in terms of the personal characteristics of the nurse, the future of the profession, and society's perceptions of the profession respectively, and there were no differences in attitudes depending on the sex variable, but a statistically significant was found depending on the year of study.The study recommended that College of Nursing must preparing programs to familiarize students with the nursing profession and its importance, focusing on the image of good nursing in the first year curriculum, developing a description for the graduate of the Faculty of Nursing and linking the college with the community. يتأثر الإقبال على دراسة مهنة التمريض بالاتجاهات التي يحملها أفراد المجتمع نحوها. فالاتجاه هو ميل عام مكتسب نسبي وعاطفي يؤثر في الدوافع النوعية للإنسان ويلعب دوراً أساسياً في توجيه السلوك نحو إنجاز الأهداف وإدراك نتائجها. لذا هدفت هذه الدراسة الوصفية إلى التعرف على الاتجاهات التي يحملها 200 طالب وطالبة من كلية التمريض في جامعة تشرين نحو مهنة التمريض والفرق في اتجاهاتهم تبعاً للمتغيرات الشخصية, تم اختيار الطلاب بطريقة العينة الطبقية العشوائية في الفترة من 12/10/2016 حتى 22/11/2016, وجمعت البيانات باستخدام استبيان مُعد مسبقاً لهذا الغرض. وجدت الدراسة بأن اتجاه الطلبة الكلي نحو مهنة التمريض كان إيجابياً بدرجة متوسطة, في حين كان ايجابياً بدرجة كبيرة في مجال النظرة الشخصية نحو المهنة, وإيجابياً بدرجة متوسطة في مجال النظرة إلى السمات الشخصية للممرض, ومستقبل المهنة, ونظرة المجتمع إلى المهنة على التوالي, ولم توجد فروق في الاتجاهات تبعاً لمتغير الجنس, ولكن وُجدت فروق هامة إحصائياً تبعاً لمتغير السنة الدراسية. وأوصت الدراسة بإعداد كلية التمريض لبرامج تعرف طلبة المدارس بمهنة التمريض وأهميتها, والتركيز على صورة التمريض الجيدة في مناهج السنة الأولى, ووضع توصيف لخريج كلية التمريض, وربط الكلية بالمجتمع.